Design and validation of an aircraft seat comfort scale using item response theory. (July 2017) - Menegon, Lizandra da Silva; Vincenzi, Silvana Ligia; de Andrade, Dalton Francisco; Barbetta, Pedro Alberto; Merino, Eugenio Andrés Díaz; Vink, Peter
Abstract: This article aims to evaluate the psychometric properties of a scale that measures aircraft seat comfort. Factor analysis was used to study data variances. Psychometric quality was checked by using Item Response Theory. The sample consisted of 1500 passengers who completed a questionnaire at a Brazilian airport. Full information factor analysis showed the presence of one dominant factor explaining 34% of data variance. The scale generated covered all levels of comfort data, from 'no comfort' to 'maximum comfort'. The results show that the passengers consider there is comfort, but this is very minimal when these passengers have to perform their desired activities. It tends to increase when aspects of the aircraft seating are improved and positive emotions are elicited. Comfort peaks when pleasure is experienced and passenger expectations are exceeded (maximum comfort). This outcome seems consistent with the literature. Further research is advised to compare the outcome of this questionnaire with other research methods, and to check if the questionnaire is sensitive enough and whether its conclusions are useful in practice. Highlights: The aircraft seat comfort scale shows evidences of validity and reliability. The IRT makes it possible to create a scale with different levels of comfort. Minimum comfort occurs when the passenger can perform the desired activities. Maximum comfort is related to pleasure feeling and to having expectations exceeded.